1991
DOI: 10.1007/bf02262732
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in bone marrow scanning

Abstract: Interest in bone marrow scanning has been renewed as the result of the development of radiopharmaceuticals for evaluating specific aspects of bone marrow anatomy, physiology and pathology. This article provides a brief review of bone marrow structure, blood flow and function essential to the understanding of basic principles of bone marrow radionuclide imaging. The prospects and limitations of imaging haematopoietic bone marrow in man using indium 111 chloride, technetium-99m (99mTc)-labelled microcolloid or 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
5

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 73 publications
(100 reference statements)
0
27
1
5
Order By: Relevance
“…Since bone marrow' reacts as a functional unit, it can be best evaluated by marrow biopsy, especially diagnostic imaging-guided biopsy [14]. However, our observations (i.e.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Since bone marrow' reacts as a functional unit, it can be best evaluated by marrow biopsy, especially diagnostic imaging-guided biopsy [14]. However, our observations (i.e.…”
Section: Discussioncontrasting
confidence: 53%
“…Recent results indicate that immunoscintigraphy with monoclonal antigranulocytic antibodies provides a highly specific and sensitive approach for the assessment of the haemopoietic status of the bone marrow [14], As the up take of these antibodies by the liver and spleen is limited, the improved image quality diminishes the interpretation problems stemming from superposition. This method has two disadvantages, however, the considerable price and the undesirable patient immunisation; the latter may re sult in risk on subsequent administration.…”
Section: Discussionmentioning
confidence: 99%
“…In these diagnostic studies no relevant binding to normal tissues other than bone marrow has been observed. 25,26 Thanks to the large number of target sites and its high affinity, the antibody rapidly and quantitatively accumulates in the marrow, thus ensuring a potent crossfire effect. 24,25,33,49,50 We felt that these advantageous properties outweighed potential disadvantages such as a lack of binding to myeloid leukaemic blasts.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-CD66 antibody (antigranulocyte, anti-nonspecific crossreacting antigen 95, BW 250/183) is well characterized with respect to biokinetic data and clinical application in bone marrow scintigraphy and localization of infections. [25][26][27] The CD66 antigen is expressed at a high density (2 ϫ 10 5 molecules per cell) on normal myelopoietic cells from the promyelocyte onward but not on AML blasts. [28][29][30][31] Aberrant expression is found on a significant fraction of CD10 ϩ acute lymphoblastic leukemia (ALL) blasts.…”
Section: Introductionmentioning
confidence: 99%
“…23,27 The anti-CD66 antibody (antigranulocyte, anti-nonspecific cross-reacting antigen 95; BW 250/183) is well characterized with respect to biokinetic data and clinical application in bone marrow (BM) scintigraphy. [28][29][30] Yttrium-90 ( 90 Y) is a ␤-particle emitter with a high energy (2.3 MeV), a maximum range of the ␤ particles of 11 mm, and a half-life of 2.7 days. 31 90 Y administration does not require isolation of patients because it does not emit ␥ radiation.…”
Section: Drug Administration and Preparative Regimen Before Hctmentioning
confidence: 99%